Clinical Study to Evaluate the Effect of Shubhdeep Kidney Care Pill in the Management of Mutrakricchra w.s.r to UTI - Sharma, Shruti; patil, Umesh; Shrivastava, Akhilesh; Raghuvanshi, Nagendra Singh (International Research Journal of Ayurveda & Yoga, 2022)
Introduction Mutrakricchra (Urinary tract infection) is a prevalent illness that affects people of all ages. Disease incidence and prevalence differ by age and gender. Urinary tract infection and its treatment are critical since it can result in immediate morbidity as well as long-term problems such as hypertension and chronic renal insufficiency. Materials and methods 30 subjects had a 45-day clinical assessment of the test drug. Patients visiting the O.P.D. and I.P.D. of the P.G. Department of Kayachikitsa, Shubhdeep Ayurveda Medical College & Hospital (P.G Institute), Indore, participated in an open clinical study. Based on inclusion and exclusion criteria, patients of both sexes between the gender of 20 and 50 years were chosen. 500mg of the trial medication were administered twice daily with lukewarm water before meals. For the purpose of observing and evaluating the therapeutic effect, a case record form was created. Results were evaluated using both subjective and objective criteria. The paired "t" test was used to statistically analyze the demographic and clinical data. Results It was observed that in the present study, highest number of patients around 50% (15) had marked mild improvement in their subjective complaints and 23% (7) had good improvement, around 20% (6) of patients showed moderate improvement and 7% showed no/ poor relief. Discussion The formulations utilized in this study have components high in madhura, tikta- ras, sita-virya, laghu, snigdha-guna, and madhura -vipaka, which aided to reduce pitta dosha and daha. Vatashaman, shothaharan, and bastishodhan are made easier by the antibacterial and antimicrobial components.